2003
DOI: 10.1152/ajpregu.00631.2002
|View full text |Cite
|
Sign up to set email alerts
|

Model of functional cardiac aging: young adult mice with mild overexpression of serum response factor

Abstract: Serum response factor (SRF) is an important transcription factor that may have a role in the maintenance of cardiac structure and function. The level of SRF mRNA expression increases approximately 16% in the hearts of mice during adult aging. To model the effect of mild SRF elevation in the aging heart, transgenic mice with low levels of SRF overexpression were generated. By 6 mo of age, the transgenic mice had a 19% increase of heart-to-body weight ratio compared with nontransgenic mice. In addition, they had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 52 publications
3
46
0
Order By: Relevance
“…We previously reported that SRF expression was increased by ϳ20% in the heart of the senescent compared with young adult rodents (5,7). In contrast, some other transcription factors, which are SRF cofactors, including Nkx2.5 and GATA4, have been reported to be decreased during adult aging (41).…”
Section: P49/strap a New Srf Cofactormentioning
confidence: 98%
See 1 more Smart Citation
“…We previously reported that SRF expression was increased by ϳ20% in the heart of the senescent compared with young adult rodents (5,7). In contrast, some other transcription factors, which are SRF cofactors, including Nkx2.5 and GATA4, have been reported to be decreased during adult aging (41).…”
Section: P49/strap a New Srf Cofactormentioning
confidence: 98%
“…The mRNA levels of a number of SRF target genes, including atrial natriuretic factor, ␣-myosin heavy chain, and sarcoplasmic reticular calcium ATPase have also been reported to undergo changes during postnatal cardiac development and during senescence (4 -7, 12-14). In a transgenic mouse model in which the human SRF gene was mildly overexpressed in the heart, cardiac changes resembling those that have been observed during adult aging in terms of myocardial function, morphology, and gene expression are observed in young adulthood (7). The mildly increased cardiac-specific SRF expression apparently up-regulates some SRF target genes, whereas it down-regulates others in the heart (7).…”
mentioning
confidence: 99%
“…42 A subsequent report showed that lower SRF expression induced a milder phenotype with evidence of accelerated cardiac aging in young transgenic mice. 43 Both studies concluded that overexpression of SRF elicits a heart failure phenotype. In this context, human heart failure was reported to show elevations of a natural dominant-negative form of SRF arising from alternative splicing.…”
Section: Srf and Cardiovascular System Disease Heartmentioning
confidence: 99%
“…Srf plays an important role in the regulation of smooth, skeletal, and cardiac muscle genes [5][6][7][8] during development and in adult life including aging. 9,10 Srf can be activated to promote transcription in response to extracellular signals that induce its association with specific cofactors. The 2 families of Srf cofactors are the TCF proteins (Elk1, SAP1, SAP2), 11 and the myocardin family of proteins that includes myocardin, megakaryoblastic leukemia 1 (Mkl1), and Mkl2.…”
Section: Introductionmentioning
confidence: 99%